2002
DOI: 10.1046/j.1365-2672.2002.01705.x
|View full text |Cite
|
Sign up to set email alerts
|

Virulence markers in Aeromonas hydrophila and Aeromonas veronii biovar sobria isolates from freshwater fish and from a diarrhoea case

Abstract: Aims: To evaluate the public health significance of representative strains of two Aeromonas spp., mainly from freshwater fish, on the basis of production of virulence-associated factors and presence of the haemolytic genes aerA and hlyA. Methods and Results: Eleven strains of Aer. hydrophila, three strains of Aer. veronii biovar sobria (all from freshwater fish) and one strain of Aer. hydrophila from human diarrhoea were tested for potential virulence traits and for the presence of the haemolytic genes aerA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
56
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 26 publications
3
56
0
4
Order By: Relevance
“…It has been reported that the aerA + /hlyA + genotype provided the best estimation of virulence for A. hydrophila in an animal model [31]. However, a study found that, when the distribution of hemolytic genes was compared to extracellular products, three genotypes (aerA + /hlyA + , aerA + /hlyA -, aerA -/hlyA -) were enterotoxic in the suckling-mouse test and had a capacity to express other virulence properties at different temperatures [32]. Pablos et al [13] In the current study, the virulence gene was not detected in 43.75% of human isolates and in 33.3% of animal isolates (in all cattle and sheep isolates).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that the aerA + /hlyA + genotype provided the best estimation of virulence for A. hydrophila in an animal model [31]. However, a study found that, when the distribution of hemolytic genes was compared to extracellular products, three genotypes (aerA + /hlyA + , aerA + /hlyA -, aerA -/hlyA -) were enterotoxic in the suckling-mouse test and had a capacity to express other virulence properties at different temperatures [32]. Pablos et al [13] In the current study, the virulence gene was not detected in 43.75% of human isolates and in 33.3% of animal isolates (in all cattle and sheep isolates).…”
Section: Discussionmentioning
confidence: 98%
“…Aeromonas spp. pose a threat to public health due to the emergence of antibiotic-resistant strains (4). In this study, the clinical Aeromonas sp.…”
mentioning
confidence: 95%
“…Copious amounts of antibiotics are used in the shrimp ponds to stimulate growth and to retard the incidence of diseases caused by overcrowded, factory farm conditions (4, 5, 9). The indiscriminate use of these antibiotics may select bacteria resistant to multiple antibiotics, and such bacteria may transfer their antibiotic resistance determinants to pathogenic bacteria (14,16).Aeromonads are ubiquitous, psychrophilic, Gram-negative microbes commonly found in fresh water, estuaries, and other coastal waters (6,7,8). They are known to cause hemorrhagic septicemia in aquatic organisms.…”
mentioning
confidence: 99%
“…Aeromonads are ubiquitous, psychrophilic, Gram-negative microbes commonly found in fresh water, estuaries, and other coastal waters (6,7,8). They are known to cause hemorrhagic septicemia in aquatic organisms.…”
mentioning
confidence: 99%
See 1 more Smart Citation